Ответы и объяснения

2014-01-21T18:32:04+04:00
Выражение: 6*x^2-5*x-4//5-x=0
 6*x^2-6*x-4/5=0
Квадратное уравнение, решаем относительно x: 
Ищем дискриминант:D=(-6)^2-4*6*(-4//5)=36-4*6*(-(4//5))=36-24*(-(4//5))=36-(-24*(4//5))=36-(-(96//5))=36+(96//5)=276//5;
Дискриминант больше 0, уравнение имеет 2 корня:x_1=(кв.корень(276//5)-(-6))/(2*6)=(кв.корень(276//5)+6)/(2*6)=(кв.корень(276//5)+6)/12=кв.корень(276//5)/12+6/12=кв.корень(276//5)/12+(1//2);x_2=(-кв.корень(276//5)-(-6))/(2*6)=(-кв.корень(276//5)+6)/(2*6)=(-кв.корень(276//5)+6)/12=-кв.корень(276//5)/12+6/12=-кв.корень(276//5)/12+(1//2).